Student pathways and differentiation policies in Ontario: are they compatible?. Issue 1 (2nd January 2020) - Young, Stacey J.; Piché, Pierre G.; Jones, Glen A.
ABSTRACT: Over the last 15 years, the government of Ontario, Canada began seeking ways to deliver and expand higher education in a more cost effective and sustainable manner through the introduction of two major policy goals: greater institutional differentiation and the expansion of student pathways. This paper will attempt to determine the compatibility of these two policy goals through a review of the relevant literature to determine if the policies are aligned from an efficiency and effectiveness, and public policy perspective. It will also identify a number of policy levers used in Ontario that may affect the extent of diversity and student pathways through document analysis, to assess their compatibility by making a limited use of the field of organisational theory as a lens to place the policies into context. It will also examine the extent to which various institutional types in Ontario have been engaged in student mobility and will compare and contrast the various strategies used to satisfy these public policy goals through textual analysis to highlight current successful institutional strategies that can be used by other jurisdictions. It will conclude with some key observations that the authors feel are necessary for either policy goal to succeed.